2001
DOI: 10.1002/app.1611
|View full text |Cite
|
Sign up to set email alerts
|

PP/clay nanocomposites: Effect of clay treatment on morphology and dynamic mechanical properties

Abstract: ABSTRACT:The morphology and properties of polypropylene (PP)/clay nanocomposites are described. The melt intercalation of organophilic clay was carried out with a single-screw extruder. The effects of two kinds of treatments of clay are discussed. Maleic anhydride (MAH)-grafted PP was used as a compatibilizer. The expansion of the intergallery distance of the clay was governed by the interaction between the clay treatment and the compatibilizer. In one case, the composites exhibited significantly reduced inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(34 citation statements)
references
References 15 publications
4
30
0
Order By: Relevance
“…Many studies have shown a nucleating effect of nanoclay for different polymers [16][17][18]. This effect can be used to enhance the mechanical and thermal properties of the polymer.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Many studies have shown a nucleating effect of nanoclay for different polymers [16][17][18]. This effect can be used to enhance the mechanical and thermal properties of the polymer.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The presence of tactoids, owing to a poor dispersion of the fi ller, was also reported to cause a decrease in spherulite size [34] . Kodgire et al . reported that, in the presence of clay, PP showed an advanced crystallization and a fi brous morphology rather than the usual spherulite behavior [35] . Similarly, a decrease in crystallinity and an increase in nucleus density was observed, owing to a nucleation effect of the clay platelets [36,37] .…”
Section: Polar and Nonpolar Polymer Systemsmentioning
confidence: 99%
“…The very strong nucleating effect of talc in PP was proved many times [64,65]. Similarly to talc, layered silicates, and especially montmorillonite (MMT), were shown to nucleate polypropylene quite strongly [66][67][68][69][70]. The influence of other fillers and reinforcements is not so clear.…”
Section: Crystalline Matrices Nucleationmentioning
confidence: 99%